Cefuroxime axetil induced DRESS in a pregnant patient - Aruna Singh; Shalini Gainder (Barpeta Obstetrics and Gynaecological Society, 2023)
Drug reaction with eosinophila and systemic symptoms (DRESS) was coined by Bocquet in who described a condition induced by drug reaction which was characterized by fever, rash, and lymph node enlargement, hematological, hepatic and other systemic involvement. A 38 year old pregnant patient presented with fever, rash and other systemic manifestations. Clinical work up was done to evaluate amongst various differential diagnosis. Patient was finally diagnosed as DRESS and successfully managed with good maternal and fetal outcome.